2001
DOI: 10.1054/bjoc.2001.1786
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of single- to double-strand DNA breaks and their absolute values determine cell death pathway

Abstract: Summary Bleomycin is a cytotoxic antibiotic that generates DNA double-strand breaks (DSB) and DNA single-strand breaks (SSB). It is possible to introduce known quantities of bleomycin molecules into cells. Low amounts kill the cells by a slow process termed mitotic cell death, while high amounts produce a fast process that has been termed pseudoapoptosis. We previously showed that these types of cell death are a direct consequence of the DSB generated by bleomycin. Here, we use deglyco-bleomycin, a bleomycin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 22 publications
0
100
0
1
Order By: Relevance
“…Single-strand DNA breaks (SSB) in very large numbers also result in cell death (Yoshida et al, 1993;CohenJonathan et al, 1999). We also reported that not only the absolute numbers of DSB or SSB but also their ratio determine cell death pathway: true apoptosis, pseudoapoptosis or mitotic cell death (Tounekti et al, 2001).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Single-strand DNA breaks (SSB) in very large numbers also result in cell death (Yoshida et al, 1993;CohenJonathan et al, 1999). We also reported that not only the absolute numbers of DSB or SSB but also their ratio determine cell death pathway: true apoptosis, pseudoapoptosis or mitotic cell death (Tounekti et al, 2001).…”
mentioning
confidence: 82%
“…This results in the generation of small abortive colonies by otherwise clonogenic cells. Mitotic cell death can be initiated by the generation of a few unrepaired DSB like those generated by small doses of ionising radiation or the internalisation of low amounts of radiomimetic drugs like BLM (Tounekti et al, 1993(Tounekti et al, , 2001Yanagihara et al, 1995).…”
mentioning
confidence: 99%
“…In the ideal case, the radiosensitizer should have no intrinsic toxicity and preferentially sensitize tumor cells to radiation. Several lines of evidence indicate that ionizing radiation kills cancer cells by induction of DNA double-strand breaks (DSBs) (Tounekti et al, 2000). Consequently, cells and animals with defects in DSB repair display increased sensitivity to ionizing radiation (Khanna and Jackson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate the role of DDR genes in seedling recovery from growth-disruptive levels of DNA damage, which we have artificially induced by exposure to ionizing radiation (IR). In this work, we have used gamma irradiation for a ubiquitous induction of DNA damage throughout the seedling, with DSBs being the most cytotoxic lesion triggered (Tounekti et al, 2001;Moiseenko et al, 2001). We have typically used an acute, transiently growth-inhibiting 150-Gy dose, which is less than that triggering a permanent growth arrest (e.g.…”
mentioning
confidence: 99%